Use of Instagram for Marketing of Ulvisa Shop Products during the COVID-19 Pandemic - Anisa Putri Amalia; Shelviana Aprilliani Nurjanah; Ully Purbandani; Dhanar Intan Surya Saputra (STMIK Pontianak, 2020)
The business market in Indonesia, for now, is benefiting greatly from the presence of Instagram social media. Instagram is an application that allows its use to share photos and videos. Instagram is a social media that can be used as marketing in the digital era to expand and increase consumer reach. Instagram makes it easy for users, especially in this case, Instagram users who use this application to promote brands or product brands. Utilizing Instagram media as a means of marketing products during the Covid-19 Pandemic is an opportunity to open an online business, where in the online shop there is no need for face-to-face contact and physical contact between sellers and buyers which is in accordance with the government's advice during the Covid-Pandemic. 19 is to keep applying physical distancing and stay at home. Along with the times, of course, new trends will emerge among the people today. Especially in terms of fashion for each individual. One of the online shops that is developing its business is Ulvisa Shop. Where Ulvisa Shop markets products in the form of women's accessories and masks, which are currently the main needs for preventing the transmission of the Covid-19 virus.